Workload Monitoring of Throwing Sport Athletes - Janel Havinga; Andrew Green; Clinton Swanepoel (Journal of Coaching and Sports Science, 2025)
Background: Throwing events involve the full use of the kinetic chain. Therefore, monitoring training loads is crucial to optimizing athlete adaptation while minimizing the risk of fatigue and long-term injury.Aims: This study aimed to determine external load using work calculations and compare them to current session internal workload metrics such as heart rate and rate of perceived exertion. Furthermore, it aimed to monitor workload over a nine-week period.Methods: Internal training load was evaluated using modes of heart rate monitoring and rate of perceived exertion. External training load was calculated as the product of throw distances and implement weight. Acute to chronic workload ratio was calculated by dividing the acute workload by the chronic workloadResults: Twenty-five throwing athletes (age: 19 (3); height: 1.82 (0) meter; mass: 93 (19) kilogram) completed 11 (7) throws in a single field session during which throwing work was calculated (Throw distance: 40.87 (17.54) meter; session-rating of perceived exertion: 198 (269) arbitrary units; Total work: 8719.37 (13960.6) Joule; Average work: 726.61 (1877.92) Joule). Correlations (p less than 0.05) were found between session rating of perceived exertion and average work (r=0.433), session duration and total (r=0.433), and average workload (r=0.523). Negative correlations existed between average heart rate and total work (r=-0.435), average work (r=-0.442), and duration. (r=-0.483). Workloads and acute to chronic workload ratio differed over the 9 weeks (p=0.025).Conclusion: Relationships were reported between calculated average work, s-RPE, session duration, and average heart rate, indicating that monitoring the duration of training sessions will be of value while changing the implement weight in the sessions.